India's Northeast and the Enigma of the Nation-state. (August 2017) - Sarmah, Bhupen
One of the major challenges before the "mainstream Indian nationalists" at the dawn of India's independence was the political integration of the "Northeast" with India envisaged as a nation-state. Some parts of the colonial frontier, such as the Naga Hills, had already witnessed a parallel nationalist discourse with the imagination of sovereignty before India's independence. With independence, the Indian nation-state project was made difficult by the geopolitical significance of the region, shaped by the experience of the partition, which separated India and Pakistan (East and West), creating a milieu of not-so-favorable international politics. The postcolonial history of the troubled periphery has been marked by an imposed notion of homogeneity and a binary of the nation-state (or the Indian mainstream) and the Northeast. Political theorists have long refuted the notion of national homogeneity. Nevertheless, the dichotomy between the plains and the valley constructed by the colonial logic was and is reinforced by the nation-state ideology, turning the periphery into a cauldron of conflict. This article engages critically with the history of conflict witnessed in the region since independence, against the backdrop of colonial interventions and the integrationist logic of the nation-state. This article argues that the political and developmental strategies, adopted by the Indian state to integrate the region, have led to the perpetuation of conflict in different forms.